Cushing's storm secondary to a rare case of ectopic ACTH secreting metastatic breast cancer - Bucciarelli, Maura (Endocrinol Diabetes Metab Case Rep, 2015)
Ectopic ACTH secretion from breast cancer is extremely rare. We report a case of a 30-year-old woman with a history of breast cancer, who presented with psychosis and paranoid behaviour. CT of the head showed white matter disease consistent with posterior reversible encephalopathy syndrome (PRES). Despite using mifepristone with multiple antihypertensives including lisinopril, spironolactone and metoprolol, she was hypertensive. Transaminitis did not allow mifepristone dose escalation and ketoconazole utilization. Etomidate infusion at a non-sedating dose in the intensive care unit controlled her hypertension and cortisol levels. She was transitioned to metyrapone and spironolactone. She was discharged from the hospital on metyrapone with spironolactone and underwent chemotherapy. She died 9 months later after she rapidly redeveloped Cushing's syndrome and had progressive metastatic breast cancer involving multiple bones, liver and lungs causing respiratory failure. LEARNING POINTS: Cushing's syndrome from ectopic ACTH secreting breast cancer is extremely rare. Cushing's syndrome causing psychosis could be multifactorial including hypercortisolism and PRES. Etomidate at non-sedating doses in intensive care setting can be effective to reduce cortisol production followed by transition to oral metyrapone.